PELAKSANAAN DIVERSI PADA SISTEM PERADILAN ANAK PERSPEKTIF KEADILAN RESTORATIF DALAM HUKUM ISLAM - Harahap, Rabiyatul Adawiyah; Bariki, Yusril (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Diversion is the transfer of settlement of child cases from the criminal justice process to processes outside the criminal justice. whether the diversion process in Law no. 11 of 2012 concerning the juvenile justice system, has it achieved the goal of restorative justice and how is diversion with a restorative justice approach reviewed into Islamic law. This research method is normative, type of literature research and the research approach is a conceptual approach, normative juridical approach, theory of restorative justice and Islamic law. The results of this study are the concept of diversion in the juvenile justice system which is contained in Law Number 11 of 2012 concerning the juvenile justice system has manifested restorative justice, diversion must be carried out not only for solving problems but for diversion. Also restore the condition of what has happened by involving all parties, both perpetrators, victims, families/guardians, society, social institutions others. Meanwhile, in Islamic law, restorative justice is also applied in Islamic law in the form of children's rights which very important because that in terms of handling children who are dealing with the law in Islamic law, legal justice and social justice and moral justice have been obtained.